Cortical Stress Reaction in Two Patients on Bisphosphonate Therapy: Case Report - Papatya TOGAY; Berna ÇELİK and Derya SOY BUĞDAYCI and Nurdan PAKER (Archives of Rheumatology, 2015)
Bisphosphonates are widely used, effective medications of documented osteoporosis. They accumulate in bone and are released for months or years despite the termination of treatment. Cortical stress reaction and related low energy atypical fractures of femoral shaft are amongst the main complications in patients with osteoporosis who are on long-term bisphosphonate therapy. Contralateral femoral cortical stress reaction may also be observed. In this article, we present two female patients who admitted to our outpatient clinic with anterior thigh pain, and review their clinical presentation. Lateral cortical thickening of both femurs were diagnosed in both patients.